Severity and distribution of bacterial leaf blight of rice in different rice growing ecosystems of Karnataka state of India - A, Raghunandana; Sunkad, Gururaj; BT, Raghavendra; Yadav, Manoj K; ST, Yanjeerappa; R, Harischandra Naik; PR, Badariprasad; D, Pramesh (ORYZA-An International Journal of Rice, 2023)
Bacterial leaf blight of rice caused by Xanthomonas oryzae pv. oryzae has posed a major threat to production-oriented farming in recent years. The yield losses caused by this pathogen are as high as 70 to 80 per cent based on the severity of the disease. A random survey was carried out in the major rice-growing ecosystem of Karnataka viz., Bhadra, Coastal, Hilly, Kaveri, Tunga Bhadra project (TBP) and Upper Krishna project (UKP) ecosystems of Karnataka during Kharif 2019. Among all the surveyed ecosystems, the highest mean per cent disease index (PDI) of 52.60 was observed in the Bhadra ecosystem, followed by 43.67 PDI in the TBP ecosystem, and the lowest PDI of 31.08 was observed under the Kaveri ecosystem. However, moderate disease severity in the range of 31.82 to 33.79 was observed under the UKP and Hilly ecosystems of Karnataka. Among the surveyed districts, the highest disease severity (62.04 PDI) was observed in Shivamogga, followed by Gadag (52.17 PDI) and Ballari (52.87 PDI) districts, and the least severity of 20.72 PDI was observed in Raichur district. However, there was no disease severity in the Coastal ecosystem of Karnataka. The disease was severe in commercial rice-growing regions compared to those where the traditional varieties were grown. The moderate rainfall areas like Bhadra and TBP ecosystem were more severely infected with BLB than the severe rainfall area like the coastal ecosystem. The present study has identified the risk-prone areas of BLB in different rice ecosystems of Karnataka.